Novel nitrogen-rich energetic macromolecules based on 3, 6-dihydrazinyl-1, 2, 4, 5-tetrazine. Issue 129 (16th December 2015) - Cohen, Adva; Yan, Qi-Long; Shlomovich, Avital; Aizikovich, Alexander; Petrutik, Natan; Gozin, Michael
Abstract : Nitrogen-rich energetic macromolecules were synthesized by reacting dihydrazinyl-1, 2, 4, 5-tetrazine (DHTz) with various diisocyanates. Abstract : Nitrogen-rich energetic macromolecules were synthesized by reacting dihydrazinyl-1, 2, 4, 5-tetrazine (DHTz) with various diisocyanates. It has been shown that polymerization or cyclization reactions could take place depending on solvent systems and reaction conditions. The formed macrocycles and polymers were comprehensively characterized by IR, NMR, high resolution MS and SEM, while the thermal stability was studied by DSC. The energetic properties of our new compounds were investigated by bomb calorimetry, along with calculations using the EXPLO-5 code. It was found that macrocycleC-DHTZ-TM and corresponding polymerP-DHTZ-TM prepared on a basis of DHTZ and tetramethylene diisocyanate have larger heats of combustion than RDX, GAP and polyGLYN.C-DHTZ-TM has a comparable density and larger detonation velocity than TNT. The nitrogen content ofC-DHTZ-TM andP-DHTZ-TM is larger than 47%. The thermal stability of DHTz-based energetic macromolecules was found to be higher than currently used energetic polymers including GAP, polyNIMMO and polyGLYN. The ADN based compositions bonded by 60% (by weight) ofP-DHTZ-HM andP-DHTZ-MB polymers have higher theoretical specific impulse than that bonded by polyGLYN. Therefore, our new compounds could be promising ingredients as energetic binders or fillers. Moreover, all of the macrocycles have potential to be used as energetic gelators in gel propellants.